The duration compression effect is mediated by adaptation of both retinotopic and spatiotopic mechanisms. (May 2016) - Latimer, Kevin; Curran, William
Abstract: The duration compression effect is a phenomenon in which prior adaptation to a spatially circumscribed dynamic stimulus results in the duration of subsequent subsecond stimuli presented in the adapted region being underestimated. There is disagreement over the frame of reference within which the duration compression phenomenon occurs. One view holds that the effect is driven by retinotopic-tuned mechanisms located at early stages of visual processing, and an alternate position is that the mechanisms are spatiotopic and occur at later stages of visual processing (MT+). We addressed the retinotopic-spatiotopic question by using adapting stimuli – drifting plaids – that are known to activate global-motion mechanisms in area MT. If spatiotopic mechanisms contribute to the duration compression effect, drifting plaid adaptors should be well suited to revealing them. Following adaptation participants were tasked with estimating the duration of a 600 ms random dot stimulus, whose direction was identical to the pattern direction of the adapting plaid, presented at either the same retinotopic or the same spatiotopic location as the adaptor. Our results reveal significant duration compression in both conditions, pointing to the involvement of both retinotopic-tuned and spatiotopic-tuned mechanisms in the duration compression effect.